Ethnomedicinal plants used by indigenous communities in Malakand District, Northern Pakistan - Hazrat Ali; Zahir Muhammad; Tahseen Ullah; Naila Inayat; Mujeeb Ur Rahman; Rahman Ullah; Ishaq Ali Shah; Shujaul Mulk Khan (Ethnobotany Research and Applications, 2026)
Background: Plants have been an integral part of human history as a source of traditional medicines. In spite of their extensive usage, ethnomedicinal plants (EMPs) of Malakand District, which is well-known for its floristic diversity, has yet to be explored. This research documented the EMPs employed by local communities to conserve indigenous knowledge and recognize plant species having therapeutic values. Methods: Field surveys were carried out at different locations of District Malakand during the summer and spring seasons of 2018-2019. Data on the EMPs were collected through interviews with 220 local informants using semi-structured questionnaires and open group discussion. Different ethnobotanical indices like informant consensus factor (ICF), fidelity level (FL), relative frequency of citation (RFC), consensus index (CI) and use values (UVs) were used for quantitative analysis of ethnomedicinal data. Results: In this study, 74 ethnomedicinal plant species, representing 65 genera and 42 families were reported. The predominant plant families included Fabaceae, Lamiaceae, Asteraceae, Berberidaceae, Apocynaceae, and Solanaceae. Based on the growth habits, herbs were the frequently used life form representing 38 species. Most of the EMPs were employed in the treatment of gastrointestinal disorders (38 species), skin disorders (23 species), and as analgesics (22 species). Leaves were the frequently used part, with pastes being the usual preparation method and oral route being the principal method of administration. The highest ICF values were found for wounds/cuts (0.65) and diabetes (0.63). Mentha longifolia and Justicia adhatoda had the highest FL values, while Dodonaea viscosa, Berberis lycium, and Calotropis procera exhibited the highest values for RFC, CI, and UV. Conclusions: The findings highlight a diverse ethnomedicinal heritage of Malakand and offers significant pharmacological potential of EMPs for future studies. Keywords: Medicinal flora; indigenous uses; quantitative indices; Malakand; Pakistan